EVALUASI PENGGUNAAN INPUT PADA USAHATANI KEDELAI DI KECAMATAN BERBAK KABUPATEN TANJUNG JABUNG TIMUR - Eva, Endra Yus; Alamsyah, Zulkifli; Napitulu, Dompak (JALOW | Journal of Agribusiness and Local Wisdom, 2020)
Soybean is one of important food sources in Indonesia. Because of demand for soybean that have not been met, so the production and productivity of soybeans still need to be enchanced. The purpose of this research was to analyze factors that affect soybean production and evaluate efficiency of aplication inputs in soybean farming in Berbak District, East Tanjung Jabung Regency. Analysis of effect of the use of production factors on production on soybean farming is done using the Cobb-Douglas function approach, using a multiple logarithmic analysis model for estimating equations. Whereas to find out the optimization of use of inputs is used the maximum profit approach. The results of the analysis of the production function obtained that the factors that significantly influence soybean production are land, seeds, Urea fertilizer, TSP, KCl, insecticides, while the use of NPK fertilizer inputs, herbicides, fungicides and labor has no effect on soybean production. Based on the results of evaluation of input use in soybean farming in Berbak Subdistrict, it can be seen that the use of land inputs, seeds, urea, TSP is not efficient, while the use of KCL fertilizer and insecticide inputs is inefficient.